Prevalenca protiteles anti-HTLV-I/II med krvodajalci v Sloveniji ter pomen pri presejalnem testiranju - Jovanovič, Petra (Zdravniški vestnik, 2008)
Background Human T-limphotropic viruses type I and II are retroviruses. Peopleinfected with HTLV-I/II are usually asymptomatic, lifelong antibodies carriers. Transfusion of blood components is one of the modes of virus transmissions. Thus, transmission can be prevented with screening of blood and/or cells, tissues, organs. Blood donor screening is performed in countrieswith high prevalence of HTLV-I/II and also in some European countries. The aim of our study was to determine the prevalence of HTLV-I/II infections in Slovenian blood donors screening and to make a decision about the implementation of blood donors screening. Methods Collected blood donations were screened for anti-HTLV-I/II by modified ELISA (ChLIA) on the Prism testing system (Abbott). Initially reactive samples were additionally tested in duplicate and also with another enzyme immunoassay Murex HTLV I+II (Abbott). Confirmatory testing was performed with immunoblot test INNO-LIA HTLV I/II Score (Innogenetics). Results Out of 9398 screened units 6 samples were initially reactive. All 6 samples were non-reactive after testing with another enzyme immunoassay Murex HTLV I+II (Abbott) and negative in confirmatory testing with immunoblot test INNO-LIA HTLV I/II Score (Innogenetics). Conclusion In our prevalence study of HTLV-I/II infections in Slovenian blood donors population we got no confirmed positive result among 9398 blood donors. The yield is as expected and is similar to other European countries. In countries with a low HTLV-I/II infectious rate, such as Slovenia, only screening of new donors, donors from endemic areas and/or donors travelling to endemic areas is rational.
Keywords: krvodajalci; presejalni testi; prevalenca; retrovirusi; virusne infekcije